2002
DOI: 10.3168/jds.s0022-0302(02)74386-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Corn Vitreousness and Ruminal In Situ Starch Degradability

Abstract: The objective of this experiment was to determine the relationship between corn kernel vitreousness and ruminal in situ starch degradation. Fourteen U.S. and five Brazilian corn hybrids cultivated in their respective countries were evaluated. The U.S. dent hybrids were harvested at one-half milk line, black layer, and 21 d after black layer stages of maturity. Brazilian flint hybrids were harvested only at the latest stage of maturity. Vitreousness was determined by manual dissection of the kernels. Ruminal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
2
45

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(219 citation statements)
references
References 12 publications
9
163
2
45
Order By: Relevance
“…Correa et al (2002) reported an endosperm vitreosity averaging 73% (64.2 to 80%) for the corn harvested in Brazil.…”
Section: Vitreousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Correa et al (2002) reported an endosperm vitreosity averaging 73% (64.2 to 80%) for the corn harvested in Brazil.…”
Section: Vitreousnessmentioning
confidence: 99%
“…Grain at higher concentrations of vitreous endosperm has lower ruminal in situ degradability, as well as lower in vitro and in vivo digestibility (CORREA et al, 2002;ALLEN et al, 2008). The ruminal degradability and intestinal digestibility of starch in dairy cows was higher for corn grain derived from cultivars with chalky endosperm (3% of the vitreous starch) in relation to cultivars with larger endosperm vitreousness (67% of vitreous starch) (TAYLOR;ALLEN, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas principais regiões produtoras de milho do mundo, o milho cultivado é quase em sua totalidade do tipo farináceo, enquanto o milho cultivado no Brasil é predominantemente do tipo duro. O milho duro apresenta reduzida degradabilidade ruminal quando comparado ao milho farináceo (Correa et al, 2002). Portanto, o processamento do milho parece ser uma Arq.…”
Section: Introductionunclassified
“…Os grãos duros são caracterizados pela predominância de endosperma ví-treo. Do ponto de vista da nutrição animal, quanto maior a proporção de endosperma vítreo menor é a digestibilidade do amido presente neste grão (CORREA et al, 2002). Neste sentido, a caracterização física de grãos de milho poderia ser útil na caracterização do valor nutritivo (PHILLIPEAU et al,1999;GIGER-RIVERDIN, 2000).…”
Section: Introductionunclassified